2021
DOI: 10.22146/ijcn.53443
|View full text |Cite
|
Sign up to set email alerts
|

The risk of inappropriate timing of complementary foods introduction is increased among first-time mothers and poor households

Abstract: Background: Global recommendations suggest mothers provide the first complementary food to infants when they reach six months of age. Failure to introduce complementary foods promptly may put infants in adverse health and nutrition outcomes. Objective: This study aimed to analyze factors associated with inappropriate timing of complementary foods introduction in Kebumen Regency. Methods: This study used a cross-sectional design. A multistage cluster sampling was employed to select 355 mothers of children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Several previous studies have found high rates of MP-ASI given to babies <6 months old. Research conducted by Puspitorini et al in Kebumen, Indonesia showed that 39.15% of toddlers were given MP-ASI at the incorrect age [10]. Breast milk contains very precise nutrients to meet the nutritional needs of babies and is easily digested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have found high rates of MP-ASI given to babies <6 months old. Research conducted by Puspitorini et al in Kebumen, Indonesia showed that 39.15% of toddlers were given MP-ASI at the incorrect age [10]. Breast milk contains very precise nutrients to meet the nutritional needs of babies and is easily digested.…”
Section: Discussionmentioning
confidence: 99%
“…The The health worker support questionnaire consists of 10 questions which are adapted from Jannah's (2015). The scoring system of health worker support is using Likert scale as a score of 1 = never, 2 = sometimes, 3 = often, and 4 = always, with the category of less support (7)(8)(9)(10)(11)(12)(13)(14), sufficient support (15-21), and good support (2-28).…”
Section: Methodsmentioning
confidence: 99%
“…It is often found, especially among mothers who are having children for the first time, at the age of 6-23 months is actually a critical period for inhibiting child growth due to the initial introduction and administration of complementary foods for their children, but unfortunately it concur mostly with the initial formation of growth faltering and accompanied with postponed neurocognitive developments; two most common condition found which could have preceded the stunting event [48]. Fortunately, this is also the time period of which diet exercises is familiarized, culturally [49].…”
Section: Loss Of Essential Amino Acids and Its Consequencesmentioning
confidence: 99%
“…Wang L et al (2019) melalui penelitiannya menjelaskan beberapa faktor yang berhubungan dengan pemberian MP-ASI dini yaitu diantaranya usia ibu yang lebih muda, tingkat pendidikan ibu yang lebih rendah, tidak adanya atau durasi menyusui yang lebih pendek, keyakinan orang tua bahwa "anak saya selalu ingin makan ketika dia melihat seseorang makan" dan kenaikan berat badan bayi dan ibu (8). Faktor lain yang berhubungan dengan pemberian MP-ASI dini adalah anak kedua atau seterusnya dan pada keluarga yang memiliki pendapatan tinggi (12).…”
Section: Pendahuluanunclassified